2008
DOI: 10.5650/jos.57.243
|View full text |Cite
|
Sign up to set email alerts
|

Aqueous Solution Properties of Disulfide Linked Gemini and Cleaved Monomeric Thiol Surfactants

Abstract: Monomeric thiol surfactants, [C n H 2n+1 N(CH 3 ) 2 CH 2 CH 2 SH]Br, were produced by the cleavage of gemini surfactant containing a disulfide bond in the spacer chain, [C n H 2n+1 N(CH 3 ) 2 CH 2 CH 2 SSCH 2 CH 2 N(CH 3 ) 2 C n H 2n+1 ]2Br. The disulfide bond was completely reduced by the addition of four times moles of dithiothreitol in water at room temperature. The critical micelle concentrations of monomeric surfactants were significantly increased in comparison with original gemini surfactants. The monom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 24 publications
1
12
0
Order By: Relevance
“…Thus the conductivity of 5 mM 2C 12 SS micelle solution will increase with increasing of monomeric C 12 SH concentration by the cleavage of disulfide bonds. In addition, the cyclic disulfide is not surface active, and is not ionic conducting species 9 . Figure 6 a shows the timecourse of conductivity for 5 mM 2C 12 SS with addition of 5 mM DTT in comparison with 5 mM 2C 10 11SS.…”
Section: Change In Conductivity Along With Cleavage Of Disulde Bondmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus the conductivity of 5 mM 2C 12 SS micelle solution will increase with increasing of monomeric C 12 SH concentration by the cleavage of disulfide bonds. In addition, the cyclic disulfide is not surface active, and is not ionic conducting species 9 . Figure 6 a shows the timecourse of conductivity for 5 mM 2C 12 SS with addition of 5 mM DTT in comparison with 5 mM 2C 10 11SS.…”
Section: Change In Conductivity Along With Cleavage Of Disulde Bondmentioning
confidence: 99%
“…We have reported that the transformation from the gemini to monomeric surfactants was performed by the addition of dithiothreitol, which is commonly used to cleave the disulfide bond into free thiols 9 . Subsequently, the produced thiol surfactants can be expected to return to the original geminis by the formation of disulfide when exposed to air.…”
mentioning
confidence: 99%
“…The production of single-tailed surfactant by cleavage of disulfide linked gemini surfactants with the addition of dithiothreitol DTT has been reported in our previous work 9,10 , shedding light on single-tailed thiol surfactants which influence the vesicular region in comparison with conventional single-tailed or gemini surfactants 11 . The critical micelle concentration CMC was determined using conduc-tivity and pyrene fluorescence probe methods.…”
Section: Introductionmentioning
confidence: 99%
“…C 12 H 25 N CH 3 3 Cl DTAC and didodecyldimethylammonium chloride DDAC were purified by repeated recrystallization from acetone. C 12 H 25 N CH 3 2 CH 2 6 N CH 3 2 C 12 H 25 2Cl C 12 -6-C 12 were synthesized using a procedure similar to the one reported previously 9 . DTT Wako Pure Chemical Industries, Ltd. was used as received.…”
Section: Introductionmentioning
confidence: 99%
“…pyrene is released during the reduction of gemini micelles into monomeric thiol surfactants upon the addition of dithiothreitol DTT , which is commonly used to cleave the disulfide bond into free thiols 8 . Moreover, the produced thiol surfactants return to the original disulfide-linked gemini form in aerated solution.…”
mentioning
confidence: 99%